Control of "blue carbon" storage by mangrove ageing: Evidence from a 66‐year chronosequence in French Guiana. (26th March 2018) - Walcker, Romain; Gandois, Laure; Proisy, Christophe; Corenblit, Dov; Mougin, Éric; Laplanche, Christophe; Ray, Raghab; Fromard, François
Abstract: The role of mangroves in the blue carbon stock is critical and requires special focus. Mangroves are carbon‐rich forests that are not in steady‐state equilibrium at the decadal time scale. Over the last decades, the structure and zonation of mangroves have been largely disturbed by coastal changes and land use conversions. The amount of time since the last disturbance is a key parameter determining forest structure, but it has so far been overlooked in mangrove carbon stock projections. In particular, the carbon sequestration rates among mangrove successional ages after (re)establishment are poorly quantified and not used in large‐scale estimations of the blue carbon stock. Here, it is hypothesized that ecosystem age structure significantly modulates mangrove carbon stocks. We analysed a 66‐year chronosequence of the aboveground and belowground biomass and soil carbon stock of mangroves in French Guiana, and we found that in the year after forest establishment on newly formed mud banks, the aboveground, belowground and soil carbon stocks averaged 23.56 ± 7.71, 13.04 ± 3.37 and 84.26 ± 64.14 (to a depth of 1 m) Mg C/ha, respectively. The mean annual increment (MAI) in the aboveground and belowground reservoirs was 23.56 × Age −0.52 and 13.20 × Age −0.64  Mg C ha −1  year −1, respectively, and the MAI in the soil carbon reservoir was 3.00 ± 1.80 Mg C ha −1  year −1 . Our results show that the plant carbon sink capacity declines with ecosystem age, while the soil carbon sequestration rate remains constant over many years. We suggest that global projections of the above‐ and belowground reservoirs of the carbon stock need to account for mangrove age structures, which result from historical changes in coastal morphology. Our work anticipates joint international efforts to globally quantify the multidecadal mangrove carbon balance based on the combined use of age‐based parametric equations and time series of mangrove age maps at regional scales. Abstract : Based on the analysis of a 66‐year chronosequence of the aboveground and belowground biomass and soil carbon stock of mangroves in French Guiana, this study shows that the plant carbon sink capacity declines with ecosystem age, while the soil carbon sequestration rate remains constant over many years. It is suggested that global projections of the above‐ and belowground reservoirs of the carbon stock need to account for mangrove age structures, which result from historical changes in coastal morphology.